Insights from an Umbrella Review of Flipped Learning in Higher Education - ElGamal, Hebatullah; Zawacki-Richter, Olaf (International Review of Research in Open and Distributed Learning, 2025)
There is a noticeable growth in the number of systematic reviews published in open, distance, and digital education (ODDE), with a growing focus on flipped teaching and learning, particularly in higher education, emphasizing the need to consolidate evidence and findings under one comprehensive review. This umbrella review aims to thoroughly understand the current state of flipped learning in higher education and pinpoint research gaps, analyzing 23 systematic reviews published between 2018 and 2022 from three international databases: Web of Science, Education Source, and Scopus. It delves into publication and authorship patterns while synthesizing key insights. The thematic scope of the reviews reveals that many were focused on the effectiveness of flipped learning and teaching interventions, as well as learning design. The review explored theories guiding practice and research, instructional design considerations, and the application of flipped classrooms in various fields of study. It also examined the reported challenges of the flipped classroom model. As there are a scarcity of theoretical frameworks and a lack of detailed information on the pedagogical challenges of this model, recommendations are presented to enhance research and practice of flipped teaching and learning. The results of this umbrella review provide valuable insights to guide research in future and improve the quality of systematic reviews in the field of ODDE in general and flipped teaching and learning in particular.